KEEFEKTIFAN MEDIA POP UP CANDI BERBANTU MODEL SNOWBALL THROWING TERHADAP PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KELAS V SDN KEMBANGARUM 02 MRANGGEN - Henry Sugiarti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The use of pop-up book media-assisted learning model throwing snowball can help teachers in teaching learning material IPS Heritage temple in Indonesia. In addition, this study aims to encourage and increase student learning outcomes V. Prior to this research grade students seem inactive and not in the spirit of learning activities. After doing research using pop-up book media-assisted learning model snowball throwing, student interest in learning began to grow and not feel bored in learning, so that student learning outcomes showed an increase in the average value of students reached the KKM. Then use the pop-up book media-assisted learning model snowball throwing increase the interest and student learning outcomes Class V